2019
DOI: 10.1016/j.chroma.2018.12.033
|View full text |Cite
|
Sign up to set email alerts
|

A single run, rapid polarity switching method for determination of 30 pharmaceuticals and personal care products in waste water using Q-Exactive Orbitrap high resolution accurate mass spectrometry

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 22 publications
1
27
2
Order By: Relevance
“…However, only Trimethoprim was detected in this study. Similar occurrence has been reported in river samples in Egypt and South Africa where Sulfamethoxazole was not detected and Trimethoprim was detected at 230 ng/L and 0.14 µg/L respectively [62,64].…”
Section: Antibioticssupporting
confidence: 85%
See 1 more Smart Citation
“…However, only Trimethoprim was detected in this study. Similar occurrence has been reported in river samples in Egypt and South Africa where Sulfamethoxazole was not detected and Trimethoprim was detected at 230 ng/L and 0.14 µg/L respectively [62,64].…”
Section: Antibioticssupporting
confidence: 85%
“…Amoxycillin was detected at 10% frequency in the water samples at concentration of 659.02 ng/L. Amoxycillin concentration in the water samples was higher than the reported concentration in Tanzanian water [61] and Egyptian water [62] but lower than the concentration reported in Chinese Pearl River [63]. A recent study in Nigeria reported an average Amoxycillin concentration of 13,300 ng/L in Lagos surface water [15].…”
Section: Antibioticsmentioning
confidence: 86%
“…Abdallah et al [206] show the UPLC-Q Exactive TM Orbitrap MS's capability for simultaneous determination of 28 acidic and basic PhACs in a single run using rapid polarity switching of the electrospray ionisation source. The PhACs belong to seven therapeutical classes, such as antibiotics, antiseptics, beta-blockers, NSAIDs, narcotic analgesics, anti-hyperglycemic, and proton-pump inhibitors.…”
Section: High-resolution Mass Spectrometry (Hrms)mentioning
confidence: 99%
“…targeted and untargeted analyses) for the presence or absence of a wide range of pollutants. Such analyses rely on the use of high-resolution accurate mass systems including, time-of-flight (TOF), quadrupole time-offlight (Q-TOF) and Orbitrap instruments (Rimayi et al 2019;Pinasseau et al 2019;Abdallah et al 2019). The use of high-resolution mass spectrometry is essential in order to obtain data on molecular ions, isotope patterns and fragment ions from the highly complex extracts, which contain numerous substances many of which will have similar molecular masses.…”
Section: Introductionmentioning
confidence: 99%